2008
DOI: 10.1097/mpg.0b013e31817fcb67
|View full text |Cite
|
Sign up to set email alerts
|

Adiponectin and Insulin Resistance in Childhood Obesity

Abstract: Adiponectin was significantly lower in obese participants than in nonobese participants in general, and it correlated significantly with fasting indices of insulin resistance and with indices derived from oral glucose tolerance tests. It is worthwhile to further investigate the option of applying a simple measurement of serum adiponectin as a screening tool before applying more time-consuming techniques in young obese individuals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
29
2
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 34 publications
4
29
2
1
Order By: Relevance
“…We found lower adiponectin levels in our patients and this is consistent with previous studies [4,33]. Previous studies suggest that hypoadiponectinemia might be involved in the development of FLD [4,24]. In our study, adiponectin levels were negatively correlated with the presence of FLD detected by the two methods.…”
Section: Discussionsupporting
confidence: 95%
“…We found lower adiponectin levels in our patients and this is consistent with previous studies [4,33]. Previous studies suggest that hypoadiponectinemia might be involved in the development of FLD [4,24]. In our study, adiponectin levels were negatively correlated with the presence of FLD detected by the two methods.…”
Section: Discussionsupporting
confidence: 95%
“…[33][34][35][36][37] In our study, parallel to the literature, adiponectin levels were found to be significantly low in the obese and overweight groups compared with the control group. Although in our research, adiponectin levels were significantly lower in the cases with insulin resistance than in the cases without insulin resistance, no significant correlations were found between adiponectin and HOMA-IR in the obese, overweight and control groups.…”
Section: Discussionsupporting
confidence: 81%
“…A number of studies have addressed the relationship between insulin resistance and adiponectin in obese children and adolescents [15,16,17]. However, there are only a few studies about the correlation between adiponectin levels and family history of T2DM in children and adolescents [18].…”
Section: Introductionmentioning
confidence: 99%